Subthreshold current model for short-channel double-gate (DG) MOSFETs with a vertical gaussian doping profile - Tiwari P.K.; Jit S. (My University, 2025)
The paper presents a short-channel subthreshold current model for the double-gate (DG) MOSFETs having Gaussian doping profile in the vertical direction of the channel. The subthreshold current is assumed to be contributed mainly by the diffusion of carriers in the subthreshold regime of operation of the device. The two gates of the device are assumed to be identical in structures for the simplicity of the model. The effects of channel length, channel doping and drain to source voltage on subthreshold current have been investigated. The asymmetric nature of the device resulted only from the location of the peak doping position of the Gaussian profile at any arbitrary position except at the middle of the channel thickness has been presented. The effect of the straggle parameter on subthreshold current of the device has also been included in the model. The proposed model is validated by comparing the theoretical results with the simulation data obtained by using the ATLAS" 2D device simulation software. Copyright © 2011 American Scientific Publishers.